Parámetros poblacionales de tres parasitoides (Hymenoptera: Scelionidae, Encyrtidae) utilizando al depredador Podisus nigrispinus (Heteroptera: Pentatomidae) como hospedero - Torres, Jorge B (1996)
The reproductive parameters of Telenomus podisi, Trissolcus brochymenae (Hymenoptera: Seelionidae) and Ooencyrtus sp. (Hymenoptera: Encyrtidae) were studied for three generations on their natural host Podisus nigrispinus (DalIas, 1851) (Hemiptera: Pentatomidaef A parasitism rate of 10 eggs/day/species was used under laboratory conditions of 27 ± lOC, 60 ± 10% RH and 14 h of photophase. No significant differences were detected between generations in terms of net reproductive mte (Ro)' intrinsic mte of natuml increase (rm), genemtion time (T) and the effect of doubling time on population inerease (DT). However, T. podisi and T. brochymenae had significantly higher RO and rm values, and lower T and DT values, with fm 1.59 and 1.50 times higher than Ooencyrtus sp., respectively. In addition Ihe former species also had shorter egg-adull period, greater longevity of females and reproduclion period ·than the other species. These results confirm the greater reproduetive potential of T. podisi and T. brochymenae, which are commonly found parasitizing P. nigrispinus.